Vaccine Hesitancy and Trust in the Scientific Community in Italy: Comparative Analysis from Two Recent Surveys - Chiara Cadeddu; Martina Sapienza; Carolina Castagna; Luca Regazzi; Andrea Paladini; Walter Ricciardi; Aldo Rosano (Vaccines, 2021)
Vaccination rates in Italy fell until 2015 because of unfounded safety concerns. Public education and a 2017 law on mandatory vaccination have boosted rates since then. The aim of our study is to explore how trust in the scientific community and attitudes towards vaccines have changed in the period of 2017–2019 in Italy. Data were extracted from the Italian section of the 2017 and 2019 editions of the European Social Survey (ESS). We compared the two surveys highlighting changes in public opinion on vaccines. A descriptive analysis of the socio-cultural variables according to the answers provided to key questions on the harmfulness of vaccines was conducted. Differences between percentages were tested by using the χ2 test. The association between the opinion about the harmfulness of vaccines and trust in the scientific community was analyzed through a logistic regression model. Compared to ESS8, ESS9 showed an increase in the percentage of respondents disagreeing with the harmfulness of vaccines. Trust in the scientific community raised in the period from 2017 to 2019 (59% vs. 69.6%). Higher education was significantly associated with disagreement regarding the harmfulness of vaccines (odds ratio (OR) = 2.41; 95% confidence interval (95%CI) 1.75–3.31), the strongest predictor was trust in the scientific community (OR = 10.47; 95% CI 7.55–14.52). In Italy, trust in the scientific community and in vaccinations has grown significantly in recent years, indicating a paradigm shift in public opinion compared to the past. Central actions and effective public communication strategies might reduce vaccine hesitancy and could be essential to garner public trust.